Cooperative Crystallization of Heterometallic Indium–Chromium Metal–Organic Polyhedra and Their Fast Proton Conductivity1. Issue 27 (15th May 2015) - Zhai, Quan‐Guo; Mao, Chengyu; Zhao, Xiang; Lin, Qipu; Bu, Fei; Chen, Xitong; Bu, Xianhui; Feng, Pingyun
Abstract Metal–organic polyhedra (MOPs) or frameworks (MOFs) based on Cr3+ are notoriously difficult to synthesize, especially as crystals large enough to be suitable for characterization of the structure or properties. It is now shown that the co‐existence of In3+ and Cr3+ induces a rapid crystal growth of large single crystals of heterometallic In‐Cr‐MOPs with the [M8L12] (M=In/Cr, L=dinegative 4, 5‐imidazole‐dicarboxylate) cubane‐like structure. With a high concentration of protons from 12 carboxyl groups decorating every edge of the cube and an extensive H‐bonded network between cubes and surrounding H2O molecules, the newly synthesized In‐Cr‐MOPs exhibit an exceptionally high proton conductivity (up to 5.8×10−2 S cm−1 at 22.5 °C and 98 % relative humidity, single crystal).